Incidence of acute-onset atrial fibrillation correlates with air temperature. Results of a nine-year survey - Ivan Comelli; Jayme Ferro; Giuseppe Lippi; Denis Comelli; Elisabetta Sartori; Gianfranco Cervellin (Springer, 2019)
Some diseases, such as renal colic, stroke, and myocardial infarction, correlate with seasonality and microclimatic variations. Although evidence is limited and controversial, a correlation between acute-onset atrial fibrillation (AAF) and seasonality has been previously reported. In order to elucidate the possible correlations between weather and incidence of AAF in a country with a temperate climate, the influence of day-by-day climate changes was analyzed based on the number of visits for AAF (defined as onset of symptoms within 48 h) in a large urban Emergency Department (ED) of northern Italy. All the episodes of AAF were retrieved from the hospital's electronic database during a period of 3287 days (January 2002 to December 2010). Only the cases whose onset occurred within 48 h from the ED visit were selected. The total number of ED visits was 725,812 throughout the observational period. Among these, 3633 AAF cases were observed, 52% of which were males. A slight but significant negative linear correlation was found between the number of AAFs and the daily temperature (R = −0.60; p = 0.001). No correlation was found between the number of AAFs and the daily humidity (R = −0.07; p = 0.2).